On Positive and Negative Altruism - Norkus, Zenonas (Problemos, 1995)
Making use of Meinong’s theory of value, the author of the paper proposes in outline the mathematical model of positive and negative altruism as behavioural dispositions. The author tries to solve the problem of interpersonal comparison of valuations. He supposes that the precondition of moral valuations of altruistic actions are not the “average” the economic valuations by the subjects and objects of these actions (as A Meinong holds), but rathcr the ethical valuations on basis of social standards of welfare.